Distinguishing Three Quality Assurance Models in Higher Education: Accreditation, Assessment and Audit - Cuong, Nguyen Huu (VNU Journal of Science: Education Research; Vol 33 No 1, 2017)
This paper analyses the similarities and differences between the world’s three most widely used higher education quality assurance models: accreditation, assessment and audit. Firstly, the paper presents an overview of the concepts related to higher education quality assurance. Next, each of the three models is discussed in detail. Finally, the paper compares the three quality assurance models. Keywords Quality assurance model, higher education, accreditation, assessment, audit References [1] Harvey, L., & Green, D., Defining quality, Assessment and Evaluation in Higher Education, Vol.18, No.1 (1993) 9. [2] Woodhouse, D., Quality and quality assurance, Quality and Internationalisation in Higher Education, OECD-IMHE, Paris, (1999) 29. [3] Vlăsceanu, L., Grünberg, L., & Pârlea, D., Quality assurance and accreditation: a glossary of basic terms and definitions, UNESCO-CEPES, Bucharest, 2007. [4] Wilger, A., Quality assurance in higher education: a literature review, Stanford University, Stanford, CA, 1997. [5] UNESCO-IIEP, External quality assurance: options for higher education managers, UNESCO-IIEP, Paris, 2006. [6] Eaton, J., An overview of U.S. accreditation, Council for Higher Education Accreditation, Washington DC, 2015. [7] Kis, V., Quality assurance in tertiary education: current practices in OECD countries and a literature review on potential effects, OECD, Paris, 2005. [8] SEAMEO RIHED, A study on quality assurance models in Southeast Asian countries: towards a southeast Asian quality assurance framework, SEAMEO RIHED, Bangkok, 2012.